On the continuum limit of fermionic topological charge in lattice gauge theory - Adams, David H. (2013)
It is proved that the fermionic topological charge of SU(N) lattice gauge fields on the four-torus, given in terms of a spectral flow of the Hermitian Wilson–Dirac operator or, equivalently, as the index of the overlap Dirac operator, reduces to the continuum topological charge in the classical continuum limit when the parameter m 0 is in the physical region 0<m 0 <2.